2019
DOI: 10.1039/c9fo01198f
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled pilot study to assess bacterial anti-adhesive activity in human urine following consumption of a cranberry supplement

Abstract: Urinary tract infections (UTIs) are one of the common bacterial infections treated with antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 48 publications
1
30
0
2
Order By: Relevance
“…The main efficacy is related to the antiadherence properties of cranberry (Ahuja et al, 1998;Liu et al, 2006) due to the A-type proanthocyanidin (PAC-A) that has been shown to be an important inhibitor of Type-I fimbriae E. coli adhesion to uroepithelial cells. Some in vitro and in vivo studies demonstrated the capacity of the cranberry to reduce the adhesion of bacteria to the cells (Ermel et al, 2012;Rafsanjany et al, 2015;Liu et al, 2019). Cranberry has also shown convincing results on motility and biofilm formation.…”
Section: Cranberry (Vaccinium Macrocarpon)mentioning
confidence: 99%
See 1 more Smart Citation
“…The main efficacy is related to the antiadherence properties of cranberry (Ahuja et al, 1998;Liu et al, 2006) due to the A-type proanthocyanidin (PAC-A) that has been shown to be an important inhibitor of Type-I fimbriae E. coli adhesion to uroepithelial cells. Some in vitro and in vivo studies demonstrated the capacity of the cranberry to reduce the adhesion of bacteria to the cells (Ermel et al, 2012;Rafsanjany et al, 2015;Liu et al, 2019). Cranberry has also shown convincing results on motility and biofilm formation.…”
Section: Cranberry (Vaccinium Macrocarpon)mentioning
confidence: 99%
“…Cranberry (Ahuja et al, 1998;Howell et al, 2005;Freitas et al, 2006;Liu et al, 2006Liu et al, , 2019AFSSA, 2007;Jepson and Craig, 2008;Pereira et al, 2011;Ermel et al, 2012;Jepson et al, 2012;Stapleton et al, 2012;Chan et al, 2013;Boonsai et al, 2014;Olczyk et al, 2014;Ulrey et al, 2014;Rafsanjany et al, 2015;Rodríguez-Pérez et al, 2016;Wojnicz et al, 2016;Pasupuleti et al, 2017;Ranfaing et al, 2018a,b;Anger et al, 2019;Bruyère et al, 2019) • Reduction of adhesion, motility, and biofilm formation…”
Section: Nutraceuticalmentioning
confidence: 99%
“…A RCT demonstrated the ability of type A proanthocyanidins of cranberry to inhibit the ex vivo adherence of both P-type and type 1 uropathogenic E. coli ( Figure 3 ) [ 76 ]. A similar result was obtained against Candida albicans strain, with a significant reduction in the adherence and biofilm formation after cranberry supplementation [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, numerous ex vivo studies have confirmed the antiadhesive activity of urine samples collected from volunteers who consumed cranberry products in comparison to urine samples collected from the placebo group. As example of this, a recent study demonstrates the strong ability of human urine after intake of a cranberry chew compared to a placebo chew to inhibit the ex vivo adherence of both P type and type 1 uropathogenic E. coli in a randomized, double-blind, placebo-controlled, crossover design pilot trial [20]. In the same way, Baron et al [59] reported a significant reduction in the adherence and biofilm formation of a Candida albicans strain by urine collected after the intake of a cranberry extract and a lecithin formulation with improved oral bioavailability.…”
Section: Antiadherence Activity Derived From Cranberry Consumptionmentioning
confidence: 99%
“…Although the consumption of cranberries (Vaccinium macrocarpon) has been extensively recommended for UTIs prophylaxis and relief of adverse symptoms, the UTIs preventive activity of cranberry has been debated in the literature and numerous clinical studies have been carried out, including some recent meta-analyses [4,12,13]. Several studies have shown a protective effect of cranberry against UTIs [14][15][16][17][18]; nevertheless, others have not found significant effects [19,20]. This current controversy about conflicting results of the clinical and cost effectiveness of cranberry supplements has been attributed to different manufactured cranberry based products and doses, as well as a lack of systematic protocol for the selection of subjects and clinical assay [13].…”
Section: Introductionmentioning
confidence: 99%